2010
DOI: 10.1096/fj.09-147926
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial mineralocorticoid receptor regulates vasoconstrictor tone and blood pressure

Abstract: Pathophysiological aldosterone (aldo)/mineralocorticoid receptor (MR) signaling has significant effects on the cardiovascular system, resulting in hypertension and cardiovascular remodeling; however, the specific contribution of the vascular MR to blood pressure regulation remains to be established. To address this question, we generated a mouse model with conditional overexpression of the MR in endothelial cells (MR-EC). In basal conditions, MR-EC mice developed moderate hypertension that could be reversed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(54 citation statements)
references
References 44 publications
0
53
0
Order By: Relevance
“…Endothelial MR is involved in inflammatory and profibrotic responses15 and the regulation of vasomotor function 16. Although these studies showed that endothelial MR does not contribute to BP regulation, overexpression of MR in the endothelium was found to affect BP 17. MR in myeloid cells and macrophages has roles in cardiac fibrosis and DOCA/salt‐induced BP elevation 18, 19.…”
mentioning
confidence: 99%
“…Endothelial MR is involved in inflammatory and profibrotic responses15 and the regulation of vasomotor function 16. Although these studies showed that endothelial MR does not contribute to BP regulation, overexpression of MR in the endothelium was found to affect BP 17. MR in myeloid cells and macrophages has roles in cardiac fibrosis and DOCA/salt‐induced BP elevation 18, 19.…”
mentioning
confidence: 99%
“…In contrast, overexpression of the MR in endothelial cells lead to a moderate increase in blood pressure in untreated mice. 4 We conclude that MR expression in endothelial cells at a physiological level does not significantly contribute to blood pressure regulation. However, when MR expression is upregulated during disease, [34][35][36] it might become more relevant for endothelial effects on blood pressure as demonstrated by experimental MR overexpression.…”
Section: Blood Pressure Regulationmentioning
confidence: 69%
“…However, when MR expression is upregulated during disease, [34][35][36] it might become more relevant for endothelial effects on blood pressure as demonstrated by experimental MR overexpression. 4 Which other cell types or mechanisms might be involved in the aldosterone effect on vascular reactivity and blood pressure? MR in vascular smooth muscle cells aggravates the vascular response to angiotensin II and the development of hypertension in aged mice.…”
Section: Blood Pressure Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…where activation leads to insertion of transporters which increase sodium and water reabsorption. The receptor is also found in non-epithelial tissues such as the heart (Sainte- Marie et al 2007), the vasculature (Nguyen Dinh Cat et al 2010, McCurley et al 2012) and adipose tissue (Caprio et al 2007, Nguyen Dinh Cat et al 2011, Briones et al 2012. Interestingly, increased MR expression in adipose tissue has been observed in obesity (Hirata et al 2012, Urbanet et al 2015.…”
Section: Introductionmentioning
confidence: 99%